2018
DOI: 10.1093/jas/skx043
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of estrus expression and intensity during a timed-AI protocol on variables associated with fertility and pregnancy success in Bos indicus-influenced beef cows1

Abstract: This experiment evaluated the impacts of estrus expression and intensity, estimated by physical activity during a timed-AI protocol, on reproductive performance of Bos indicus-influenced beef cows. A total of 290 lactating, primiparous, and multiparous nonpregnant Nelore × Angus cows received a 2 mg injection of estradiol benzoate and an intravaginal progesterone (P4) releasing device (CIDR) on d -11, a 12.5 mg injection of PGF2α on d -4, CIDR removal in addition to 0.6 mg injection of estradiol cypionate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 63 publications
(113 reference statements)
2
7
0
7
Order By: Relevance
“…Furthermore, the average percentage of estrous incidence in this study can be categorized as high (more than 70%). As the cows received GnRH and PGF2α synchronization, this number is logical and similar to the previous report showing more than 70% of estrous expression in cows treated with similar synchronization protocol (Rodrigues et al, 2018). The estrous expression is particularly affected by the increasing level of circulating estradiol hormone, which induces the hypothalamic initiation leading to the onset of estrous expression (Silper et al, 2015;Schubach et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the average percentage of estrous incidence in this study can be categorized as high (more than 70%). As the cows received GnRH and PGF2α synchronization, this number is logical and similar to the previous report showing more than 70% of estrous expression in cows treated with similar synchronization protocol (Rodrigues et al, 2018). The estrous expression is particularly affected by the increasing level of circulating estradiol hormone, which induces the hypothalamic initiation leading to the onset of estrous expression (Silper et al, 2015;Schubach et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Em estudos similares, observou-se a influência do comportamento de estro sobre as dimensões luteais e os níveis séricos de progesterona no período pós-ovulatório, sugerindo, assim, a existência de uma correlação entre expressão do estro e parâmetros morfofuncionais luteais [34,35,43]. Deste modo, a mensuração da vascularização, nesta estrutura ovariana, pode fornecer importantes informações sobre a função luteal e o índice de fertilidade em fêmeas bovinas [8,12,28,48].…”
Section: Discussionunclassified
“…Sá Filho et al [46], buscando avaliar a influência do estro sobre o diâmetro luteal de vacas submetidas a IATF, constatou distinções entre as fêmeas que apresentaram estro e as que não demostraram estro, obtendo média de 22,9 ± 3,0 mm e 20,3 ± 3,9 mm, respectivamente. De forma similar, Rodrigues et al [43] averiguaram que as fêmeas que apresentavam o comportamento do estro antes do momento da inseminação propriamente dita, também, apresentaram maiores dimensões luteais.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…These findings support Løvendahl and Chagunda (2010), who Aungier et al (2012) also found an association between BCS and estrous expression, where a 0.25 increase in BCS was associated with increased physical activity before ovulation. The reduction in estrogen-dependent estrous behavior, caused by a temporary state of negative energy balance, has also been noted in beef cows (Rodrigues et al, 2018).…”
Section: Parity Milk Production and Bcsmentioning
confidence: 90%